Innovation in Sustainable Packaging in the US Market: A Case Study of Shenzhen Kindvast Paper Display Products Co., Ltd. - Weizhao Huang (Journal of World Economy, 2025)
With the increasing global focus on environmental protection, sustainable packaging has become a significant trend in the packaging industry. The demand for sustainable packaging in the US market is continuously growing, driven by consumer preferences for eco-friendly packaging and relevant regulations. This paper takes Shenzhen Kindvast Paper Display Products Co., Ltd. (hereinafter referred to as “Kindvast”) as an example to explore how the company meets the sustainable packaging needs of the US market through innovative design and technology application. The study finds that Kindvast has successfully developed packaging solutions that meet both environmental standards and commercial demands by using recyclable materials, biodegradable materials, and developing patent technologies, such as “A High-Strength Paper Box with Moisture and Mildew Resistance” and “A Printing and Spraying Device for Paper Box Processing with Uniform Coating.” Through case analysis, this paper demonstrates the significant impact of Kindvast’s innovative practices in reducing environmental impact and enhancing customer satisfaction. Finally, the paper concludes the significance of Kindvast’s innovation practices in sustainable packaging for the US market and proposes future development directions for sustainable packaging and Kindvast’s potential contributions.